Ignition systems for gasoline engines : 3rd International Conference, November 3-4, 2016, Berlin, Germany - Günther, Michael; Sens, Marc (Springer, 2016)
The volume includes selected and reviewed papers from the 3rd Conference on Ignition Systems for Gasoline Engines in Berlin in November 2016. Experts from industry and universities discuss in their papers the challenges to ignition systems in providing reliable, precise ignition in the light of a wide spread in mixture quality, high exhaust gas recirculation rates and high cylinder pressures. Classic spark plug ignition as well as alternative ignition systems are assessed, the ignition system being one of the key technologies to further optimizing the gasoline engine.
Keywords: Internal combustion engines -- Ignition -- Congresses.; elektronické knihy; electronic books